TREATMENT OF DIARRHOEA USING TRADITIONAL MEDICINES: CONTEMPORARY RESEARCH IN SOUTH AFRICA AND ZIMBABWE - Maroyi, Alfred (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Gastrointestinal disorders, diarrhoea in particular remain a major concern in South Africa and Zimbabwe resulting in high mortality rates when left untreated. This investigation was aimed at documenting herbal medicines used in the treatment of diarrhoea in South Africa and Zimbabwe. Materials and Methods: A review of literature on plant species used as remedies for diarrhoea in South Africa and Zimbabwe was undertaken by the use of different electronic databases such as Google Scholar, ScienceDirect, Scopus as well as library searches at the University of Fort Hare, South Africa and the National Herbarium of Zimbabwe (SRGH) in Harare, Zimbabwe. Results: This study reported ten plant species most widely used to treat diarrhoea in South Africa and Zimbabwe. Of the lot, Sclerocarya birrea (A. Rich.) Hochst. was the most popular medicinal plant used as antidiarrhoeal remedy (11 literature citations) in South Africa and Zimbabwe, followed by Elephantorrhiza elephantina (Burch.) Skeels and Schotia brachypetala Sond. with eight literature citations each. The roots (47.4%) are the most frequently used plant parts, followed by bark (26.3%), leaves (21.1%) and rhizomes (5.3%). Conclusion: The documented antidiarrhoeal activities of this repository of selected plant species against diarrhoea causing agents such as rotavirus, Escherichia coli, Shigella, Campylobacter, Giardia, Entamoeba histolytica, Salmonella, Yersinia and Vibrio cholerae calls for further investigation aimed at isolating phytochemical compounds responsible for antidiarrhoeal activities, their mode of action, and also establish their safety and efficacy. This cross-cultural acceptance of antidiarrhoeal herbal medicines and the use of the same plant species in different geographical zones serve as an indication of the importance of herbal medicines in primary healthcare of local communities.